Neuropeptides and peptide hormones identified in codling moth, Cydia pomonella (Lepidoptera: Tortricidae). Issue 4 (4th July 2019) - Garczynski, Stephen F.; Hendrickson, Christopher A.; Harper, Artemus; Unruh, Thomas R.; Dhingra, Amit; Ahn, Seung‐Joon; Choi, Man‐Yeon
Abstract: The codling moth, Cydia pomonella, is a worldwide pest of pome fruits. Neuropeptides regulate most physiological functions in insects and represent new targets for the development of control agents. The only neuropeptides reported from the codling moth to date are the allatostatin A family peptides. To identify other neuropeptides and peptide hormones from codling moth, we analyzed head transcriptomes, identified 50 transcripts, and predicted 120 prepropeptides for the codling moth neuropeptides and peptide hormones. All transcripts were amplified, and these sequences were verified. One of the notable findings in this study is that diapause hormones (DHs) reported from Tortricid moths, including the codling moth, do not have the WFGPRL sequence in C‐terminal ends in the pban genes. The C‐terminal motif is critical to characterize insect DH peptides, and always conserved in pban/dh genes in Lepidoptera and many insect orders. Interestingly, the WFGPRL sequence was produced only from the capa gene in the codling moth. The allatostatin A‐family encoding transcript predicted nine peptides, seven of which, as expected, are identical to those previously isolated from the moth. We also identified new codling moth orthologs of insect neuropeptides including CCHamides, allatostatin CC, RYamides, and natalisins. The information provided in this study will benefit future codling moth investigations using peptidoproteomics to determine peptide presence and functions. Abstract : Codling moth diapause hormone (DH) and pheromone biosynthesis activating neuropeptide (PBAN).